1997
DOI: 10.1152/jappl.1997.83.1.323
|View full text |Cite
|
Sign up to set email alerts
|

Decreased [3H]ouabain binding sites in skeletal muscle of rats with chronic heart failure

Abstract: Abnormalities intrinsic to skeletal muscle are thought to contribute to decrements in exercise capacity found in individuals with chronic heart failure (CHF). Na+-K+-adenosinetriphosphatase (the Na+ pump) is essential for maintaining muscle excitability and contractility. Therefore, we investigated the possibility that the number and affinity of Na+ pumps in locomotor muscles of rats with CHF are decreased. Myocardial infarction (MI) was induced in 8 rats, and a sham operation was performed in 12 rats. The deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…Our findings of the effects of CHF on Na ϩ -K ϩ -ATPase content (␤ max ) are similar to what has been reported previously in the Sol muscles of rats with CHF (22,38,45). Interestingly, the absolute values we report for ␤ max in Sol in Con rats and rats with severe CHF are nearly identically to those previously published (38).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings of the effects of CHF on Na ϩ -K ϩ -ATPase content (␤ max ) are similar to what has been reported previously in the Sol muscles of rats with CHF (22,38,45). Interestingly, the absolute values we report for ␤ max in Sol in Con rats and rats with severe CHF are nearly identically to those previously published (38).…”
Section: Discussionsupporting
confidence: 91%
“…A unique feature of our study, which does not appear to have been properly addressed in previous studies examining skeletal muscle Na 45), it was expected that changes in the catalytic activity of the enzyme would parallel the changes in Na ϩ -K ϩ -ATPase content. However, we have found that only in the case of the LV was the association maintained in CHF.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This may explain why a tissue distal from the heart is also affected. This is the case for skeletal muscle from rats subjected to MI in which ouabain sites were reduced even though their affinity was not different (36,39). Furthermore, our results demonstrate that the inotropic response to ouabain was Ca 2+ -dependent in the Sham group.…”
Section: Discussionsupporting
confidence: 53%
“…To date only a few studies have examined muscle Na + -K + -ATPase changes with the disease. There is evidence that in experimental CHF in rats, Na + -K + -pump content (βmax), as measured with [ 3 H] ouabain binding, is decreased in muscles composed primarily of slow-oxidative and fast-oxidative glycolytic fibres, but not in muscles composed of fast-glycolytic fibres (Musch et al, 2002;Pickar et al, 1997). The reductions in βmax occurred in the absence of changes in the dissociation constant (K d ) (Musch et al, 2002;Pickar et al, 1997), suggesting that there is no change in Na + -K + -ATPase enzyme population type.…”
Section: Membrane Excitability Na + -K + -Atpase Expression and Dismentioning
confidence: 99%